Increasing Returns and Path Dependence in the Economy - W. Brian Arthur; Kenneth J. Arrow (United States: The University of Michigan Press, 1994)
Brian Arthur's work establishes a whole new domain for economics, a new perspective on many contemporary economic problems, and an explanation for many puzzling features of the high technology economy. This book provides the ideal introduction to and a comprehensive exposition of Arthur's work.
(NP(B/11261s
Keywords: inductry -- location -- economy